Smart working during the COVID-19 pandemic: the prevalence of musculoskeletal and visual disorders in administrative staff of a large international company - Santoro, Paolo Emilio; Amantea, Carlotta; Travaglini, Martina; Salin, Gianluca; Borelli, Ivan; Rossi, Maria Francesca; Hashemain, Dariush Khaleghi; Galuano, Maria Rosaria; Moscato, Umberto (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. During the COVID-19 Pandemic, the use of digital devices during work activities has increased with important repercussions on the psychological and physical well-being of the employees. The aim of this study was to investigate the prevalence of musculoskeletal and visual disorders related to the use of computers and home workstation. Methods. The study is a cross-sectional study. A checklist, from the National Institute of Health, was administered to white collar workers of a large international pharmaceutical company based in Italy. Results. Our study showed that postural breaks have a protective effect on neck/shoulder pain (OR 0.32, CI 0.16-0.62), back and lower extremity pain (OR 0.35, CI 0.18-0.69), and eye burning (OR 0.50, CI 0.27-0.94) of study participants. Conclusions. The research recommends that remote employees who often change their workstations should establish a suitable work environment and obtaining enough risk training from an occupational physician. This is essential for maintaining their mental and physical well-being.